Study of CdTe detector response functions using different MCNPX computational modeling detailing - A. M. Antunes; B. M. Mendes; P. L. Squair; M. S. Nogueira; A. T. Almeida-Jr; M. A. S. Lacerda (Brazilian Journal of Radiation Sciences, 2024)
The spectra measured with cadmium telluride (CdTe) detectors show high spectral distortions that must be corrected by applying a mathematical algorithm along with the detector's response functions. Simplified computational modeling of the CdTe detector is generally used to obtain its response functions. In this work, the Monte Carlo code MCNPX was used to study the response functions of a CdTe detector using more complex detector modeling and compared it with those obtained by simplified modeling. Raw spectra were corrected using the response matrices obtained for the simplified and detailed modeling of the CdTe and compared with those obtained with reference-validated software.